CURRENT ISSUES OF PATHOLOGIC ANATOMY IN CASE OF EMERGENCY AT THE PRESENT STAGE OF MEDICINE DEVELOPMENT - I. E. Galankina (Неотложная медицинская помощь, 2016)
Current issues of pathologic anatomy in case of emergency at the present stage of medicine development.